EFFICACY OF COGNITIVE BEHAVIORAL THERAPY ON ANXIETY LEVELS IN ACID ATTACK VICTIMS IN LAHORE, PAKISTAN (The Research of Medical Science Review, 2025)
This case illustrates the efficacy of Cognitive Behavioral Therapy as psychological management of anxiety disorder amongst acid attack victims. Assessment was done formally through anxiety subscale from Depression Anxiety Stress Subscale (DASS’21) short form, while interview and Dysfunctional Thought Record Sheet (DTR) was taken as an informal means of assessment. According to the scores obtained by both the clients on DASS’21 scale as well as DTR, both met the criteria for anxiety based on DSM 5TR. Psychotherapeutic intervention comprised of Cognitive Behavioral Therapy and was based on “Khushi aur Khatoon”, a culturally adapted Cognitive Behavioral Therapy Manual. Post assessment showed marked improvement amongst the symptoms of clients, as evident by scores obtained on DASS’21 scale after the intervention.Keywords: acid attack, acid attack victims, anxiety, cognitive behavioral therapyFarouq (2005) defined acid attack as, “violence involving throwing acid at a person’s body to disfigure and scar the person for life”; most acid attacks are targeted towards face to damage the appearance (Gulrez, 2016). Nitric acid, sulfuric acid and hydrochloric acid are commonly used acids for this purpose (Patel, 2014). Mittal et al. (2021) highlights the importance of face as an important component of identity since that helps with identification. Hence, the vengeful motive behind most of these acid attacks is to target the victim’s face to permanently scar their physical appearance (Khoshnami et al., 2017) as well as target their identity (Cleary et al., 2018).The theme of acid attacks is a concern for Pakistan in the recent era. Even though acid attacks were deemed illegal and unlawful in 2010 with passing of Acid Control and Acid crime Prevention Bill, Pakistan is one of the countries with highest number of acid attack crimes with an increase in attacks registered every year (Soomro,2015). As reported by Human Rights Commission of Pakistan around 400 women are reported with acid attack complains annually. Furthermore, as highlighted by Zulifqar et al. (2021) 60% acid attacks are not reported due to various cultural and societal factors.Not only does the act of acid attacks contribute to severely harmful medical impacts, but additionally plethora of social, psychological, and economic impacts on the victim’s life (Qazi et al., 2019). Patel (2014) highlighted how the consequences of acid attack include “blindness, permanent scarring of face and body, as well as social, psychological and economic difficulties.”. As mentioned by Farouk (2005) while the physical aspects of acid attack include disfiguration of facial features and melting of bones, the psychological impact includes lifelong stigmatization, lower self-esteem and self-isolation. Insomnia, depression, apprehension of another attack, anxiety, shame and loneliness are some of the psychological impacts of this crime (Zulifqar et al., 2021).As defined in Cognitive therapy of anxiety disorders (Clark & Beck, 2011) “Anxiety is a complex cognitive, affective, physiological and behavioral response system (i.e., threat mode) that is activated when anticipated events or circumstances are deemed to be highly aversive because they are perceived to be unpredictable, uncontrollable events that could potentially threaten the vital interests of an individual”.Aim The aim of the study was to investigate the efficacy of cognitive behavioral therapy on reducing the anxiety level amongst acid attack victims in Lahore. The results drawn are based on two acid attack individuals using quasi experimental research design.Hypothesis There is likely to be a significant difference in the levels of anxiety before and after receiving intervention in form of cognitive behavioral therapy among acid attack victims in Lahore, Pakistan.Method Research Design For this research aiming to look at the efficacy of cognitive behavioral therapy on reducing anxiety levels amongst acid attack victims of Lahore, a quasi-experimental research design was used. This study had within-subjects group designSample Participants were recruited through non-probability purposive sampling technique.Participants The initial plan was to have a sample of 24 participants with 12 in control group and 12 in experimental group. However, later, due to the sample being a minority, it was decided that participants will be recruited for one group i.e. experimental group and a pre and post assessment will be carried out to assess the effectiveness of therapy. Total number of participants for this research was two and these participants were admitted at Jinnah burn ward.Setting This research was carried out at Jinnah Hospital Burn Unit, Lahore Pakistan. The setting for the current intervention study was individualistic sessions. Based on a general CBT module, the minimum number of sessions conducted were eight.Materials Demographic Form. Depression Anxiety Stress (Short Form): Anxiety subscale